Hyperhomocysteinemia is Associated with Aortic Atheroma Progression in Stroke/TIA Patients - Sen, Souvik; Reddy, P Leema; Grewal, Raji P.; Chang, Patricia; Hinderliter, Alan (Frontiers in Neurology, 2010)
Significance: Aortic arch (AA) atheroma and AA atheroma progression are independent risk factors for recurrent vascular events in stroke/transient ischemic attack (TIA) patients. Total homocysteine level (tHcy) is an independent risk marker for atherosclerosis including that found in AA. The purpose of this study was to prospectively test the association between AA atheroma progression and tHcy. Methods: This is a cohort study of 307 consecutive hospitalized stroke/transient ischemic attack (TIA) patients undergoing transesophageal echocardiogram (TEE) as a part of their clinical workup. Measurable AA atheroma was detected in 167 patients of whom125 consented to a protocol-mandated follow-up TEE at 12 months. Patients had evaluation for vascular risk factors, dietary factors (folate, B12 and pyridoxine), and methylene tetrahydrofolate reductase (MTHFR) polymorphism. One-hundred-eighteen stroke/TIA patients had tHcy, acceptable paired AA images, and detailed plaque measurements. An increase by ≥1 grade of AA atheroma was defined as progression. Results: Of the 118 patients, 33 (28%) showed progression and 17 (14%) showed regression of their index arch lesion at one year. tHcy (≥14.0 µMol/L) was significantly associated with progression on both univariate (RR=3.4, 95% CI 2.0-5.8) and multivariate analyses (adjusted RR=3.6, 95% CI 2.2-4.6). The changes in AA plaque thickness (r2=0.11; p<0.001) and AA plaque area (r2=0.08; p=0.002) correlated with tHcy. tHcy was associated with change in plaque thickness over 12-months, independent of age, dietary factors, renal function and MTHFR polymorphism (Standardized β-coefficient 0.335, p=0.02). Conclusions: Our results validate the association and a linear correlation between tHcy and progression of AA atheroma.